A Method for Investigating Coverage Area Issue in Dynamic Networks - Mundher, Zaid (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Coverage area in dynamic networks is considered an important issue that affects their general performance. It also affects the delay time when exchanging data and the consumption of resources in the network. Moreover, the coverage area issue in dynamic networks is directly affected by the distributions of nodes within the environment. Movement patterns may also affect the performance when it comes to coverage area. Therefore, this work develops a method that simulates different scenarios. These scenarios include a variety of settings and parameters that are believed to affect the coverage area issue of dynamic networks. These experiments enable network developers to be aware of the optimal conditions that maximize the coverage area of dynamic network nodes and eventually improve the overall performance of the network. Three distributions are used in the experiments namely, Cauchy distribution, Power-Law distribution, and Normal distribution. Also, the simulations incorporate the correlation mobility model for nodes dynamics. The findings show that Cauchy distribution is not appropriate for simulating dynamic networks due to the large uncovered areas by nodes communications. Also, the stability of an approach is considered an important factor when measuring the performance of a dynamic network. The results of this research are important to avoid wasting network resources.